Study of hydrocarbons in brown seaweed macrocystis pyrifera - Acha de la Cruz, Otilia (1998)
Samples of algae M. pyrifera of different sites along sraits of Pucusana, San Bartolo and Ancon, were collected, and made studies of hydrocarbons, being identified the presence of n-alkanes constituted mainly by paraffins of n-C15H32 until n-C30H62. The procedure involved saponification process of lipids and hydrocarbons insolation in n-hexane, purification in silica gel chromatography and identifaction with gas chromatography. The results showed significant differences of the composition of hidrocarbons in the different sampes, being obtained information related to the posible contamination with the petroleum; the hydrocarbons seem be derived of biogenic land and marine sources, evidenced with a strong odd carbon in the n-alkanes.